Thiocyanate and Organic Carbon Inputs Drive Convergent Selection for Specific Autotrophic Afipia and Thiobacillus Strains Within Complex Microbiomes - Huddy, Robert J.; Sachdeva, Rohan; Kadzinga, Fadzai; Kantor, Rose S.; Harrison, Susan T. L.; Banfield, Jillian F. (Frontiers in Microbiology, 2021)
Thiocyanate (SCN–) contamination threatens aquatic ecosystems and pollutes vital freshwater supplies. SCN–-degrading microbial consortia are commercially adapted for remediation, but the impact of organic amendments on selection within SCN–-degrading microbial communities has not been investigated. Here, we tested whether specific strains capable of degrading SCN– could be reproducibly selected for based on SCN– loading and the presence or absence of added organic carbon. Complex microbial communities derived from those used to treat SCN–-contaminated water were exposed to systematically increased input SCN concentrations in molasses-amended and -unamended reactors and in reactors switched to unamended conditions after establishing the active SCN–-degrading consortium. Five experiments were conducted over 790 days, and genome-resolved metagenomics was used to resolve community composition at the strain level. A single Thiobacillus strain proliferated in all reactors at high loadings. Despite the presence of many Rhizobiales strains, a single Afipia variant dominated the molasses-free reactor at moderately high loadings. This strain is predicted to break down SCN– using a novel thiocyanate desulfurase, oxidize resulting reduced sulfur, degrade product cyanate to ammonia and CO2 via cyanate hydratase, and fix CO2 via the Calvin–Benson–Bassham cycle. Removal of molasses from input feed solutions reproducibly led to dominance of this strain. Although sustained by autotrophy, reactors without molasses did not stably degrade SCN– at high loading rates, perhaps due to loss of biofilm-associated niche diversity. Overall, convergence in environmental conditions led to convergence in the strain composition, although reactor history also impacted the trajectory of community compositional change.